1971
DOI: 10.1073/pnas.68.5.964
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inactivation of 16S Ribosomal RNA Induced by Colicin E3 In Vivo

Abstract: Treatment of sensitive Escherichia coli cells with colicin E3 leads to inactivation of 30S ribosomal subunits. In vitro reconstitution of 30S subunits indicates that the E3-induced defect lies solely in the 16S RNA. 16S RNA from E3-treated cells lacks several T1 RNase oligonucleotides of normal 16S RNA, including the one from the 3'-end of the 16S RNA, as analyzed by the fingerprint technique of Sanger. An RNA fragment about 50 nucleotides long has been isolated from E3-treated cells. This RNA contains the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
1

Year Published

1972
1972
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(150 citation statements)
references
References 27 publications
7
142
1
Order By: Relevance
“…This report deals with the sequence of these 2 bands. Our data are almost in complete agreement with the components found by Bowman et al [2], in the colicin E3 released fragment but not with the sequence reported by Ehresmann et al [3] , for the terminal 38 nucleotides in the 3'-OH end of the 16 S RNA.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…This report deals with the sequence of these 2 bands. Our data are almost in complete agreement with the components found by Bowman et al [2], in the colicin E3 released fragment but not with the sequence reported by Ehresmann et al [3] , for the terminal 38 nucleotides in the 3'-OH end of the 16 S RNA.…”
Section: Introductionsupporting
confidence: 86%
“…Fhresmann et al have not reported on the purity of their 3'-OH fragment, so it is not possible to judge whether this may account for the difficulties. The possibility remains that there are strain differences, since there are minor differences between our results and those of Bowman et al [2] on the composition of the E3 fragment.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations